Contribution-based profit-sharing scheme for joint ventures - Hsueh, Sung-Lin; Yan, Min-Ren (Technological and Economic Development of Economy, 2011)
Along with globalization of the construction market, international construction firms often choose to cooperate with local construction firms in the form of Joint Ventures (JV) when they enter into the domestic markets of different countries. In this way, they cannot only reduce investment risks, but also enhance production efficiency, reduce costs and generate more profits. The conventional method of profit-sharing between JV firms is based on ratio of investment. However, as the firms make different contributions to the project, the rationality of such a profit-sharing method is often doubtful and thus is difficult to maintain a stable cooperative relationship for a JV team. Based on the concept of the cooperative game theory, this paper proposes a contribution-based profit-sharing model using Shapley Value. A case study is used to describe how firms can use this model to reach decisions of participation, and determine a fair profit-sharing rule after cooperation to enhance mutual trust and create the advantages of cooperation. Article in English. Pelno pasidalijimo tarp įmonių schema, pagrįsta patirtomis išlaidomis Santrauka. Vykstant statybos rinkos globalizacijai, tarptautinės statybos įmonės, patekusios į vietinę kitos šalies rinką, dažnai linkusios bendradarbiauti su vietos statybos įmonėmis. Jos gali ne tik sumažinti investicijos riziką, bet ir padidinti gamybos efektyvumą, sumažinti išlaidas ir gauti didesnį pelną. Tradicinis pelno pasidalijimo metodas tarp įmonių grindžiamas investicijų santykiu. Tačiau kai įmonių įnašas į projektą skirtingas, toks pelno metodo racionalumas dažnai abejotinas, todėl tokiu atveju yra sunku palaikyti stabilų įmonių bendradarbiavimą. Remiantis lošimų teorijos koncepcija, šiame darbe siūlomas pelno pasidalijimo modelis naudojant Shapley reikšmę. Skaitmeniniu pavyzdžiu rodoma, kaip įmonės gali taikyti šį modelį priimdamos sprendimus dėl dalyvavimo bendroje veikloje ir teisingo pelno pasidalijimo. Taip sustiprinamas tarpusavio pasitikėjimas ir sukuriamos bendradarbiavimo prielaidos. Reikšminiai žodžiai: pelno pasidalijimas, bendra įmonė, bendradarbiavimas, strateginis aljansas, lošimų teorija, Shapley vertė.